(untitled) (Teacher’s World: Journal of Education and Research, 2023)
The coronavirus epidemic brought our education system to a standstill. It created a sense of uncertainty among students, teachers, and researchers. After almost 13 months, we are publishing the new issue of this journal. We hope it will help disseminate new knowledge about education to build a knowledge society. This editorial intends to get answer to the questions, "What was the effect of COVID-19 on Bangladesh education?" and "What will be the strategy to mitigate the loss caused by the pandemic?" A total of 13 article out of 28 have been considered to be published. The results of the articles shows the difficulties for Bangladeshi university students to continue online teaching and learning because of the lack of compatible devices to students and also for their inability of not afford to procure data for accessing the internet. Reviewing the result6s of the studies published supports us in deciding about effective strategies for online and blended education in the various educational sub-sectors of Bangladesh. Some of the findings claim that online education will be successful only if the required facilities are provided to all students by the authority or government. Otherwise, severe discrimination will emerge in Bangladesh’s education system between poor and financially well-off students. Then the editorial presents the context and background of IER and the teacher’s world. It advocates for conducting research with appropriate need-based paradigms that would be effective in dealing with post-pandemic challenges in higher education, and it provides a glimpse of all 12 articles that have been published. It also acknowledges the role of Teachers’ World in strengthening knowledge and research in the field of education. The world of teachers saw the COVID-19 pandemic as an once-in-a-lifetime opportunity for IER to conduct research and publish in order to create knowledge for addressing various issues in the Bangladesh education system caused by the pandemic crisis. Thus, IER takes a proactive stance, suggesting that education must respond not only to the past, not even to the present, but to future needs. Teacher’s World: Journal of Education and Research, Vol. 48(2), Dec 2022, p.1-9